Phenological and Morphological Analysis of Elite Wheat [Triticum aestivum L.] Genotypes under Normal Irrigated Conditions - Panthi, Binod; Kunwar, Priyanka; Poudel, Mukti Ram (AGRIVITA Journal of Agricultural Science, 2025)
Phenological and morphological traits, environmental conditions, and management practices influence the grain yield of bread wheat. Twenty elite wheat genotypes were evaluated under irrigated conditions using an alpha lattice design with two replications at IAAS, Paklihawa, Nepal, in 2021–2022 to identify key yield-attributing traits. Among 11 phenological and morphological traits, days to booting (DTB), plant height (Ph), spike length (SL), and number of spikelets per spike (NSPS) showed high heritability and genetic advance. Phenotypic correlation revealed significant (P<0.01) negative associations of grain yield (GY) with DTB (-0.434), days to heading (DTH, -0.411), and Ph (-0.411). Principal component and biplot analyses highlighted DTB, DTH, days to anthesis (DTA), and Ph as key traits negatively correlated with GY. Path analysis demonstrated a direct negative effect of DTB (-0.745) and Ph (-0.336) on GY, while DTH (0.131) and DTA (0.104) had positive effects, offset by DTB’s indirect influence. Thus, early booting and shorter plant height are recommended for achieving high yields. Cluster analysis grouped genotypes into five clusters, with cluster 2 (BL 4407, BL 4919, NL 1346) and cluster 5 (NL 1350) identified as promising candidates for developing dwarf and earlybooting varieties in irrigation-based breeding programs respectively.